Mechanochemical Synthesis of Cesium Titanium Halide Perovskites Cs2TiBr6-xIx (x=0, 2, 4, 6) - Kupfer, Christian; Elia, Jack; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Crystal Research and Technology, 2022)
Perovskite materials have a great variety of applications, such as X-ray detection, lasing and piezoelectric, or solar energy harvesting. While achieving record efficiencies, perovskite solar cells suffer from the presence of toxic lead in their crystal structure. One possibility to circumvent this issue is via the family of vacancy-ordered double-perovskites, where lead atoms are replaced alternatingly by a tetravalent atom and a vacant lattice site. From this material family, Cs2TiBr6 has recently emerged as a promising candidate due to its favorable reported properties for photovoltaic applications specifically. This paper presents a novel and facile synthesis route to obtain phase-pure Cs2TiBr6 and its lesser-studied iodine-based relatives Cs2TiBr4I2, Cs2TiBr2I4, and Cs2TiI6 via high-energy mechanochemical ball milling. The materials are characterized with structural, microscopic, and photophysical techniques to reveal indirect bandgaps with values of 1.88, 1.13, 1.04, and 1.02 eV but also a distinct lack of any significant photoluminescence (PL) and a high instability under ambient conditions. These findings enable us to clarify the previously controversial properties of Cs2TiBr6 and establish its role in the vast landscape of perovskite photovoltaics.
CRIS-Team WoS Importer:2022-11-25
Keywords: ball milling; cesium titanium halides; lead-free; stability